Experimental tests on shallow foundations of onshore wind turbine towers. (7th February 2022) - Lago, Bruno Dal; Flessati, Luca; Marveggio, Pietro; Martinelli, Paolo; Fraraccio, Giancarlo; di Prisco, Claudio; di Prisco, Marco
Abstract: The current effort towards the progressive switch from carbon‐based to renewable energy production is leading to a relevant spreading of both on‐ and off‐shore wind turbine towers. Regarding reinforced concrete shallow foundations of onshore wind turbine steel towers, possible reductions of reinforcement may increase their sustainability, speed of erection, and competitiveness. The article presents the results of an experimental program carried out at Politecnico di Milano concerning both cyclic and monotonic loading, simulating extreme wind conditions on 1:15 scaled models of wind turbine steel towers connected by stud bolt adapters to reinforced concrete shallow foundations embedded in a sandy soil. Three couples of foundation specimens were tested with different reinforcement layouts: (a) similar to current praxis, (b) without shear reinforcement, and (c) without shear reinforcement and with 50% of ordinary steel rebars replaced by steel fibers. Additional vertical loads were added to the small‐scale models in order to ensure similarity in terms of stresses. The test results allowed to (i) characterize the mechanical behavior of the foundation element considering soil‐structure interaction under both service and ultimate load conditions, (ii) assess the foundation failure mode, (iii) highlight the role of each typology of reinforcing bars forming the cage, and (iv) provide hints for the optimization of these latter.